92.0k views
21 votes
How do i solve this?

How do i solve this?-example-1
User Kennethvr
by
5.5k points

1 Answer

6 votes

Answer:

y = 6

Explanation:

You solve by using the pythagorean theorem, which is:


a^(2) +b^(2) =c^(2)

Where a and b are legs of the triangle, and c is the hypotenuse, or y in this case. So let's rearrange this equation for c:


c=\sqrt{a^(2) +b^(2) }

Now, we can substitute in the known values and solve:


c=\sqrt{3.6^(2) +4.8^(2) } = √(36) = 6

Therefore, the value of y is 6

Hope this helps!

User Omar Elabd
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.